School Inventory Management Using Android Based QR code - Miftahul Ulum; Siti Sufaidah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Inventory management of school facilities is an essential part of asset management to ensure the availability, condition, and effective use of items. However, manual inventory recording often leads to data inaccuracies, difficulties in tracking, and consumes a significant amount of time and effort. Therefore, this study aims to design and develop a mobile application based on Android to assist the inventory management process of school facilities more efficiently and accurately by utilizing QR Code technology. The application is developed using Java/Kotlin programming language and Android Studio framework, with SQLite used for local data storage and PHP-MySQL for data synchronization to the server when connected to the internet. The main features include inventory data input, QR Code generation and printing, QR Code scanning for item tracking, item condition updates, and damaged or repair-needed item reporting. The system is also equipped with user authentication to ensure that only administrators have access to the data. The testing results show that the application runs well on Android devices and is capable of managing inventory data more quickly and accurately compared to manual methods. The integration of QR Codes facilitates instant item identification through scanning, thereby accelerating the recording and checking processes. Thus, this application is expected to be a practical and efficient solution for inventory management in school environments.